SRE transformation for operator core network maintenance - Yun XU; Bingbai HUANG; Zuohui LI; Jie HUANG (Dianxin kexue)
With the rapid development of core network technology,network structures have become increasingly complicated.Nowadays,it is urgent to transform from the traditional CT core network to IT core network.Widely used in the IT field,SRE model provided core network maintenance personnel with an applicable transformation way.The feasibility of SRE model through the CT maintenance point of view was analyzed,emphasizing on the comparison of IT maintenance with CT maintenance in reality with principles mentioned in SRE.Moreover,cases were expounded in the thesis to demonstrate an effective transformation strategy with the help of SRE model.